2023
DOI: 10.1021/acsomega.2c07769
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-Tuned Reduced Graphene Oxide@Zn/Cu: Benign Materials for the Cleanup of Selected Nonsteroidal Anti-inflammatory Drugs in Water

Abstract: The persistent increase in the amount of nonsteroidal anti-inflammatory drugs such as ibuprofen (IBP) and diclofenac (DCF) in water bodies is alarming, thereby calling for a need to be addressed. To address this challenge, a bimetallic (copper and zinc) plantain-based adsorbent (CZPP) and reduced graphene oxide modified form (CZPPrgo) was prepared by facile synthesis for the removal of ibuprofen (IBP) and diclofenac (DCF) in water. Both the CZPP and CZPPrgo were characterized by different techniques such as Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…35,36 The major shortcomings of these technologies are the high cost of operation and the production of secondary by-products, which may be more toxic and complex. 37,38…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 The major shortcomings of these technologies are the high cost of operation and the production of secondary by-products, which may be more toxic and complex. 37,38…”
Section: Introductionmentioning
confidence: 99%
“…35,36 The major shortcomings of these technologies are the high cost of operation and the production of secondary by-products, which may be more toxic and complex. 37,38 According to research reported by various scientists over the years, adsorption techniques have proven to be one of the most promising approaches for removing SEs from water because they are cheap, easy, environmentally benign and do not lead to the production of secondary by-products. 27,38 This paper presents a review of the use of adsorption technology for the removal of SEs from water; it comprehensively examines the old status, current status and the future of this research topic through a detailed systemic review and largescale bibliometric analysis performed based on information search on the ISI web of science search engine using the keywords "steroid estrogen (s)", "removal", "adsorbents", article citation, author's collaboration, country, annual outputs, etc., with the majority of published research works spanning the last 50 years (1973-2022).…”
Section: Introductionmentioning
confidence: 99%
“…TrOCs include herbicides, pharmaceuticals, antibiotics, personal care products, steroid hormones, parabens, anions, and toxins produced by bacteria. Some of these contaminants are toxic to aquatic and human life at low concentrations owing to their mutagenicity, carcinogenicity and teratogenicity 10‐13 . The associated effects of these contaminants include impaired reproductive ability, disrupted endocrine system and sometimes death 14‐17 …”
Section: Introductionmentioning
confidence: 99%
“…Some of these contaminants are toxic to aquatic and human life at low concentrations owing to their mutagenicity, carcinogenicity and teratogenicity. [10][11][12][13] The associated effects of these contaminants include impaired reproductive ability, disrupted endocrine system and sometimes death. [14][15][16][17] Heavy metals, which include lead, mercury, copper, zinc, chromium, cadmium and arsenic, are non-biodegradable, which leads to their accumulation in the environment 4 and may be passed along the food chain.…”
Section: Introductionmentioning
confidence: 99%
“…Different technologies have been explored for the sequestration of dissolved phosphate from water, which include advanced biological treatment, chemical precipitation, ion exchange, electrodialysis, membrane filtration, electro-coagulation, and adsorption [9][10][11][12][13][14][15][16][17][18][19][20][21]. The major shortcomings of some of these techniques include the operational cost, difficulties in operation, and limited versatility.…”
Section: Introductionmentioning
confidence: 99%